Assessing landslide vulnerability in Kohima city, Nagaland: A geospatial approach - Kedovikho, Yhoshu; Krishnaiah, Y.V. (National Geographical Journal of India, 2022)
Kohima located in the Eastern Himalaya of Northeast India experience numerous landslides and soil creeps annually. Landslides, the resultant of various interactions i.e., geological, geomorphologic, meteorological factors etc., caused immense loss economically and environmentally. Kohima city experiences torrential amount of rainfall which further aggravate landslide hazard. This paper implores the use of high-resolution satellite data for deciphering landslide vulnerability mapping through remote sensing and GIS technique. Factors such as land use and land cover, lithology, lineament, drainage, road, aspect and slope were used as thematic input layers for landslide vulnerability mapping. Bivariate statistical method particularly Information Value method was used to extract the information from the landslide and the various controlling factors to generate the landslide vulnerability map. Validation of the landslide vulnerability mapping using classification and R-index methods along with ground observation were used to create the final vulnerability map.